Analysis of Solvency and Profitability on the Financial Health of PT Bank Syariah Indonesia Tbk for the Period 2021–2024: Analisis Solvabilitas dan Profitabilitas Terhadap Kesehatan Bank pada PT Bank Syariah Indonesia Tbk Periode 2021-2024 - Astuti, Kadek Ayu Puja; Santoso, R. Tri Priyono Budi; Trimurti, Christimulia Purnama (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2025)
The banking sector plays a crucial role in supporting national economic stability by mobilizing public funds and channeling them to productive activities. PT Bank Syariah Indonesia Tbk, the largest Islamic bank in Indonesia formed through the merger of three state-owned Islamic banks, requires an assessment of its financial soundness during its early operational period. This study aimed to evaluate the financial health of PT Bank Syariah Indonesia Tbk from 2021 to 2024 using solvency and profitability ratios. Solvency was measured by the Capital Adequacy Ratio (CAR) and Debt to Asset Ratio (DAR), while profitability was assessed using the Net Interest Margin (NIM) and Return on Equity (ROE). The study employed a quantitative descriptive method with purposive sampling, using secondary data from the bank’s annual financial reports. The results indicate that CAR remained in the "very healthy" category for four consecutive years, reflecting strong capital adequacy. DAR showed an increasing trend but stayed within the "very unhealthy" to "unhealthy" categories, indicating that the funding structure is not yet optimal. NIM was classified as very healthy, despite a slight decline in efficiency over the last two years, while ROE showed a positive trend, moving from "less healthy" to "moderately healthy." Overall, the financial condition of PT Bank Syariah Indonesia Tbk demonstrates good stability with potential for sustainable growth following the merger.